2020
DOI: 10.1371/journal.pone.0227346
|View full text |Cite
|
Sign up to set email alerts
|

Persistent severe acute respiratory distress syndrome for the prognostic enrichment of trials

Abstract: Background Acute respiratory distress syndrome (ARDS) is heterogeneous. As an indication of the heterogeneity of ARDS, there are patients whose syndrome improves rapidly (i.e., within 24 hours), others whose hypoxemia improves gradually and still others whose severe hypoxemia persists for several days. The latter group of patients with persistent severe ARDS poses challenges to clinicians. We attempted to assess the baseline characteristics and outcomes of persistent severe ARDS and to identify which variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This finding is important because evidence both before and during the COVID-19 era showed that, among patients with ARDS, oxygenation on the third day after intubation may be more strongly associated with mortality than oxygenation on the day of intubation. 16,17 Also, the occurrence of bacteremia among survivors was 57.1% (8 of 14) in the full vaccination group vs 73.9% (65 of 88) in the control group, and, although statistically insignificant, this difference in occurrence might be associated with different mortality rates between groups. 18…”
Section: Jama Network Open | Critical Care Medicinementioning
confidence: 88%
“…This finding is important because evidence both before and during the COVID-19 era showed that, among patients with ARDS, oxygenation on the third day after intubation may be more strongly associated with mortality than oxygenation on the day of intubation. 16,17 Also, the occurrence of bacteremia among survivors was 57.1% (8 of 14) in the full vaccination group vs 73.9% (65 of 88) in the control group, and, although statistically insignificant, this difference in occurrence might be associated with different mortality rates between groups. 18…”
Section: Jama Network Open | Critical Care Medicinementioning
confidence: 88%
“…In fact, over half of the resolving HRF patients in our study had PaO 2 :FIO 2 < 150 at baseline, indicating that many patients who begin their ICU course with serious respiratory failure improve quickly. The prognostic value of this early trajectory, and the disconnect between initial severity of respiratory failure and subsequent outcomes, has not previously been investigated in acute HRF but has been described in ARDS [10,21,[45][46][47]. Notably, a secondary analysis of randomized trial data showed patients with ARDS that rapidly improved within 1 day had substantially lower mortality than patients with persistent ARDS and that 63% of rapidly improving ARDS patients were moderate or severe at enrollment [10].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with respiratory failure requiring mechanical ventilation are weaned off within three days [19], while others may develop worsening lung injury and/or excessive fibroproliferation contributing to prolonged need for mechanical ventilation and hypoxemia [20]. Using trajectories of clinical and biologic data to classify subphenotypes has helped identify patients at high risk for poor outcomes in such heterogeneous conditions as chronic obstructive pulmonary disease, pneumonia, and acute kidney injury, and can help determine early biologic events that contribute to subsequent clinical course [10,[21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…Patients with persistent severe ARDS have poor clinical outcomes. Identifying this kind of patients at trial enrollment can be an approach to personalized medicine [29].…”
Section: Sars and Mersmentioning
confidence: 99%